2016
DOI: 10.1371/journal.pone.0164066
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Cardiac Ischemia-Reperfusion Injuries in Opa1+/- Mouse Model

Abstract: BackgroundRecent data suggests the involvement of mitochondrial dynamics in cardiac ischemia/reperfusion (I/R) injuries. Whilst excessive mitochondrial fission has been described as detrimental, the role of fusion proteins in this context remains uncertain.ObjectivesTo investigate whether Opa1 (protein involved in mitochondrial inner-membrane fusion) deficiency affects I/R injuries.Methods and ResultsWe examined mice exhibiting Opa1delTTAG mutations (Opa1+/-), showing 70% Opa1 protein expression in the myocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 39 publications
3
44
0
Order By: Relevance
“…SIRT3, a target of PGC‐1α, plays an important role in the suppression of ROS and mitochondrial biogenesis (Kong et al , ). Previous studies found that three mitochondrial fusion genes, OPA1, MFN1 and MFN2, significantly increased the efficiency of oxidative respiratory chain to protect tissue from injury (Hall et al , ; Le Page et al , ). DRP1 and FIS1 are two key proteins controlling mitochondrial fission (Hu et al , ; Marín‐García and Akhmedov, ).…”
Section: Resultsmentioning
confidence: 99%
“…SIRT3, a target of PGC‐1α, plays an important role in the suppression of ROS and mitochondrial biogenesis (Kong et al , ). Previous studies found that three mitochondrial fusion genes, OPA1, MFN1 and MFN2, significantly increased the efficiency of oxidative respiratory chain to protect tissue from injury (Hall et al , ; Le Page et al , ). DRP1 and FIS1 are two key proteins controlling mitochondrial fission (Hu et al , ; Marín‐García and Akhmedov, ).…”
Section: Resultsmentioning
confidence: 99%
“…Fis1 is a small protein that is located of Drp1. On the contrary, mitochondrial fusion is mediated by the action of outer-membrane mitofusins mitofusin gene 1 and mitofusin gene 2 (Mfn1 & 2) and inner-membrane optic atrophy factor 1 (Opa1) (Le Page et al, 2016). In the presence of various stress, Drp1 translocates from the cytosol to the outer mitochondrial membrane (OMM) and divides a mitochondrion into two pieces via GTP hydrolysis (Flippo and Strack, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Upon I/R, cardiomyocytes from cardiac‐specific Mfn2 knock‐out mice show a great loss of mitochondrial membrane potential and a significant decrease in survival ratio, indicating that Mfn2 down‐regulation promotes cardiomyocyte apoptosis (Zhao et al, ). OPA1 mutant induces more cardiomyocyte death exposed to I/R challenge (Chen et al, ) and after subjection to I/R, Opa1 +/− mice display significantly greater infarct size in myocardium than the control group (Le Page et al, ). Remote ischemic preconditioning up‐regulates the expression of OPA1 to preserve well‐shaped elongated mitochondria, thereby reducing myocardial infarct size (Cellier et al, ).…”
Section: The Role Of Mitochondrial Fusion and Fission In Cardiomyocytmentioning
confidence: 99%